Application of HepaRG mono- and HepaRG:THP-1 cocultures as immune responsive hepatotoxicity models - Gijs J.J. van Slobbe; Mathias Busch; Wouter Bakker; Coen Govers; Hans Bouwmeester (Toxicology, 2026)

NLRP3 inflammasome activation by particles and fibers: implications for human hazard assessment - Mathias Busch; Gerrit Bredeck; Hans Bouwmeester; Roel P. F. Schins (Archives of Toxicology, 2026)
The NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome has been shown to be involved in the manifestation of adverse effects following exposure to occupational, dietary and environmental particulate matter. In this review, we summarize knowledge on NLRP3 inflammasome activation by particles and fibers in vitro and in vivo, outline dominant activation mechanisms and discuss the link to human diseases. While the association between NLRP3 activation and development of diseases is well established for occupational exposure to mineral dusts like asbestos and quartz, the health effects of low-level exposure to environmental particulate pollutants, such as micro- and nanoplastics, desert dust or novel nanocomposites remain to be unraveled. Based on the combined literature of well-studied and emerging particles, we emphasize the relevance of testing for NLRP3 activation in the hazard assessment of novel particulate materials.

Pro-inflammatory response of human iPSC-derived intestinal epithelial monolayers towards microbial toxins LPS and nigericin - Germaine Aalderink; Hugo Brouwer; Jingxuan Wang; Aafke W. F. Janssen; Meike van der Zande; Coen Govers; Tamara Hoppenbrouwers; Hans Bouwmeester; Mathias Busch (Archives of Toxicology, 2026)
The intestinal epithelium forms a selective barrier between the intestinal lumen and the subepithelial layer. Intestinal epithelium plays a critical role in initiating inflammatory tissue responses in vivo, which remains challenging to emulate in vitro. Caco-2 cells are commonly used models of the intestinal epithelium, but lack crucial receptors and pathways associated with pro-inflammatory reactions. Human-induced pluripotent stem cell (iPSC)-based in vitro models are assumed to provide a system that better emulates in vivo responses. This study evaluated the inflammatory response of iPSC-derived intestinal epithelial cells (IEC) and Caco-2-derived intestinal epithelial cells to the microbial toxins lipopolysaccharide (LPS) and nigericin. Here, iPSCs were differentiated towards enterocyte, goblet- and Paneth-like cells without using three-dimensional culture techniques. The formed monolayer barriers were exposed to a combination of 0–100 µM nigericin and 100 ng/mL LPS on either the apical or basolateral side. The treatment-induced expression of cytokine genes and cytokine secretion were compared between the iPSC-derived cell model and differentiated Caco-2 cell layers. Nigericin exposure in combination with LPS significantly reduced transepithelial electrical resistance in the iPSC-derived model, and resulted in a tenfold increased secretion of the pro-inflammatory cytokines interleukin (IL)-6, IL-8, and tumor necrosis factor-alpha compared to the negative control. A similar increase was observed for the mRNA expression of these cytokines. No significant effect on TEER, cytokine secretion, or mRNA expression was observed in the Caco-2 model. Overall, this study shows that iPSC-IECs are a more sensitive model compared to Caco-2 to emulate inflammatory perturbations of the human intestinal epithelium.

Toxicity of true-to-life microplastics to human iPSC-derived intestinal epithelia correlates to their protein corona composition - Hugo Brouwer; Mathias Busch; Shuo Yang; Tom Venus; Germaine Aalderink; Juan Francisco Ferrer Crespo; Aliro Villacorta; Alba Hernández; Irina Estrela-Lopis; Sjef Boeren; Hans Bouwmeester (Journal of Hazardous Materials, 2025)

Understanding the interplay of depositional rock types, mineralogy, and diagenesis on reservoir properties of the coal-bearing Langsettian and Duckmantian strata (Bashkirian, Pennsylvanian) of the Ruhr Area, NW Germany - Jonas Greve; Benjamin Busch; Dennis Quandt; Mathias Knaak; Christoph Hilgers (International Journal of Earth Sciences, 2024)

Elevated risk of adverse effects from foodborne contaminants and drugs in inflammatory bowel disease: a review - Tom Walraven; Mathias Busch; Jingxuan Wang; Joanne M. Donkers; Marjolijn Duijvestein; Evita van de Steeg; Nynke I. Kramer; Hans Bouwmeester (Archives of Toxicology, 2024)
The global burden of Inflammatory bowel disease (IBD) has been rising over the last decades. IBD is an intestinal disorder with a complex and largely unknown etiology. The disease is characterized by a chronically inflamed gastrointestinal tract, with intermittent phases of exacerbation and remission. This compromised intestinal barrier can contribute to, enhance, or even enable the toxicity of drugs, food-borne chemicals and particulate matter. This review discusses whether the rising prevalence of IBD in our society warrants the consideration of IBD patients as a specific population group in toxicological safety assessment. Various in vivo, ex vivo and in vitro models are discussed that can simulate hallmarks of IBD and may be used to study the effects of prevalent intestinal inflammation on the hazards of these various toxicants. In conclusion, risk assessments based on healthy individuals may not sufficiently cover IBD patient safety and it is suggested to consider this susceptible subgroup of the population in future toxicological assessments.

Interlaboratory comparison of an intestinal triple culture to confirm transferability and reproducibility - Angela A. M. Kämpfer; Ume-Kulsoom Shah; Shui L. Chu; Mathias Busch; Veronika Büttner; Ruiwen He; Barbara Rothen-Rutishauser; Roel P. F. Schins; Gareth J. Jenkins (In vitro models, 2022)
The development and improvement of advanced intestinal in vitro models has received increasing attention in recent years. While the availability of relevant in vitro models is pivotal to advance the replacement and reduction of animal use in research, their robustness is a crucial determinant for intra- and interlaboratory reproducibility. We have developed a standard protocol to build a triple culture model combining two types of human intestinal epithelial cells (Caco-2, HT29-MTX-E12) and macrophages (THP-1), which was tested for transferability and reproducibility between three laboratories. The epithelial tissue barrier development and triple culture stability were investigated as well as the models’ responses to the non-steroidal anti-inflammatory drug diclofenac in terms of barrier integrity, cytotoxicity, and cytokine release. The results of two partner laboratories were compared to previously established benchmark results and quality criteria. For the epithelial co-cultures, the results were overall highly comparable between the laboratories. The addition of THP-1 cells resulted in increased variability and reduced reproducibility. While good correlation was achieved in several endpoints, others showed substantial response differences between the laboratories. Some variations may be addressed with training or demonstrations, whereas others might be related to fundamental differences in the cell lines introduced during routine cell culture and maintenance. Our results underline the importance of interlaboratory transfer studies using standardised experimental procedures, including defined quality criteria and benchmarks, as well as of training when newly establishing complex in vitro models in laboratories.

Cell cycle arrest in early mitosis and induction of caspase-dependent apoptosis in U937 cells by diallyltetrasulfide (Al2S4) - Claudia Cerella; Christiane Scherer; Silvia Cristofanon; Estelle Henry; Awais Anwar; Corinna Busch; Mathias Montenarh; Mario Dicato; Claus Jacob; Marc Diederich (Apoptosis, 2009)

Effect of verapamil on tachycardia-induced early cellular electrical remodeling in rabbit atrium - Roman Laszlo; Christoph Winkler; Stefan Wöhrl; Ralf E. Wessel; Sara Laszlo; Mathias C. Busch; Jürgen Schreieck; Ralph F. Bosch (Naunyn-Schmiedeberg's Archives of Pharmacology, 2007)